2023
DOI: 10.1212/wnl.0000000000207133
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Approaches to Inherited Metabolic Pediatric Epilepsies

Abstract: Treatment options for inherited metabolic epilepsies are rapidly expanding with advances in molecular biology and the genomic revolution. Traditional dietary and nutrient modification, and inhibitors or enhancers of protein and enzyme function, the mainstays of therapy, are undergoing continuous revisions to increase biological activity and reduce toxicity. Enzyme replacement, and gene replacement and editing hold promise for genetically targeted treatment and cures. Molecular, imaging and neurophysiologic bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Commensurate with these seminal findings, derived from flumazenil positron emission tomography scans and paired‐pulse transcranial magnetic stimulation studies in our patient population, we found that dramatic changes occur over time in the elevated metabolite levels in these patients, specifically with previously unknown reductions and normalization of GABA and GHB levels over the first decade 9 . This manifestation of a chronic overuse‐related compensatory response has generalized applicability and profound implications for attempts to develop gene therapy targeted to the optimal timing, dose, and even cell target 10,11 …”
Section: Figuresupporting
confidence: 75%
See 1 more Smart Citation
“…Commensurate with these seminal findings, derived from flumazenil positron emission tomography scans and paired‐pulse transcranial magnetic stimulation studies in our patient population, we found that dramatic changes occur over time in the elevated metabolite levels in these patients, specifically with previously unknown reductions and normalization of GABA and GHB levels over the first decade 9 . This manifestation of a chronic overuse‐related compensatory response has generalized applicability and profound implications for attempts to develop gene therapy targeted to the optimal timing, dose, and even cell target 10,11 …”
Section: Figuresupporting
confidence: 75%
“…9 This manifestation of a chronic overuse-related compensatory response has generalized applicability and profound implications for attempts to develop gene therapy targeted to the optimal timing, dose, and even cell target. 10,11 Such ontogenetic effects of changes over time in a neurodevelopmental disorder, along with superimposed compensatory physiologic changes, lay at the heart of The presence and severity of epilepsy in the condition, as well as the onset and severity of autism, correlate with the measured reductions in the metabolites and with age. 12,13 In contrast to nonsyndromic autism, the diagnostic criteria for autism are met in this patient population when they reach the end of the first decade, thus accentuating how we must account for changes in the developing nervous system, and adaptations to these changes, in both normal development and neurological disease.…”
mentioning
confidence: 99%
“…Gene replacement therapy has emerged as a central strategy in the field of gene therapy and has shown great promise in the treatment of certain pediatric cancers ( Pearl et al, 2023 ). The thrust of this approach is to identify a particular mutated gene in a tumor and use viral vectors to deliver a normal, “wild type” version of that gene to the cancer cells ( Bhattacharjee et al, 2022 ).…”
Section: Overview Of Gene Therapy In Pediatric Cancermentioning
confidence: 99%
“…Although in certain cases conditions are treatable and controllable, 9 relevant therapies are likely to require life‐long administration and provide limited efficacy. Encouragingly, emerging treatment paradigms for IDNT are shifting from symptom‐based, supportive, or palliative approaches to disease‐modifying, directly targeting the disease‐causing mechanisms 10 …”
Section: Introductionmentioning
confidence: 99%